Influence of natural organic matter on membrane capacitive deionization performance. (February 2021) - Shim, Jaegyu; Yoon, Nakyung; Park, Sanghun; Park, Jongkwan; Son, Moon; Jeong, Kwanho; Cho, Kyung Hwa
Abstract: Membrane capacitive deionization (MCDI) is a prospective desalination technology that removes ions using an electric potential difference across charged porous carbon electrodes. Natural organic matter (NOM) in feed water could influence the electrochemical process by leading to pore-blockages or forming a cake layer on the ion-exchange membrane-coated porous carbon electrode, thereby hindering ion removal. In this study, we explored the influence of different types of NOM, namely, humic acid (HA) and tannic acid (TA), on the MCDI desalination process for feed waters with inorganic salts (NaCl and CaCl2 ). HA significantly interfered with the adsorption process and reduced the salt removal rate by up to 68% in the case of NaCl-based feed water. However, the influence of HA on salt removal in the case of CaCl2 -based feed water was marginal owing to the formation of a charge-neutralized complex, which was caused by the egg-box effect between Ca 2+ and HA. TA reduced removal rates of salts (NaCl and CaCl2 ) by 37% and 60%, respectively. This is because of the lower molecular weight and smaller hydrodynamic diameter of TA relative to that of HA, owing to which TA exhibits a stronger adhesion to the electrode pore structure. Furthermore, as TA substantially reduces MCDI performance with regard to the adsorption of inorganic salts, its presence in feed water results in higher electrical resistance and energy consumption. Graphical abstract: Image 1 Highlights: Natural Organic Matters (NOMs) affected membrane capacitive deionization (MCDI). Salt removal and energy consumption of MCDI were highly reliant on types of NOMs. NOMs with inorganic salts were retained in an MCDI cell over time. Proposed model was satisfactory to describe the effluent concentration on MCDI.